Етиката на смртта - Неил, Томас (Identities: Journal for Politics, Gender and Culture, 2022)
Author(s): Томас Неил Title (Macedonian): Етиката на смртта Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 122-135 Page Count: 13 Citation (Macedonian): Томас Неил , "Етиката на смртта,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 122-135.